MAGNETIC STRATIGRAPHY AND BIOSTRATIGRAPHY OF PLIOCENE ARGILLE- AZZURRE (NORTHERN APENNINES, ITALY) - CHANNELL JET; POLI MS; SPROVIERI R; VILLA G.; RIO, DOMENICO (Elsevier BV:PO Box 211, 1000 AE Amsterdam Netherlands:011 31 20 4853757, 011 31 20 4853642, 011 31 20 4853641, EMAIL: nlinfo-f@elsevier.nl, INTERNET: http://www.elsevier.nl, Fax: 011 31 20 4853598, 1994)
An integrated biomanetostratigraphic chronology for the Mediterranean Pliocene has been developed in the last five years mainly from land sections in Southern Italy (Calabria and Sicily) and ODP Leg 107 (Tyrrhenian Sea) cores. In this paper, the chronology is applied to terrigenous sediments from the Northern Apennine foredeep where reworking, as well as sedimentation rate and facies variations, limit the resolution of biostratigraphy and physical stratigraphy. The integrated chronology gives improved stratigraphic control for a Messinian to Upper Pliocene section exposed on the banks of the Stirone near Parma (Northern Italy) and for a short Lower Pliocene section located nearby at Sant'Andrea Bagni. The sections are in the vicinity of stratotype sections for the tabianian (Lower Pliocene) and Piacenzian (Upper Pliocene), and the chronology gives new insights into the complex Pliocene sedimentation history in the Northern Apennine foredeep at this time. At the Stirone section, the base of the Pliocene record is in a normal polarity chronm correlated to the Thvera subchron, indicating a hiatus at the Miocene/Pliocene boundary and the absence of the MPL1 foraminiferal zone. At Sant'Andrea Bagni, MPL1 is also missing, in contrast to previous reports. We conclude that this biozone is probably absent throughout the Northern Apennines where post-Messinian flooding appears to have occurred at the onset of MPL2 time. During the Gilbert Chron, sedimentation rates at Stirone reached 104 cm/kyr, as nearly 300 m of "argille azzurre" (blue clay) were deposited in less than 0.5 Myr. Very sporadic sedimentation is apparent from the Late Nunivak to the top of the section (late Gauss Chron), with a number of hiatuses being recognized within Chron 2Ar (late Gilbert) and in the early Gauss. This interruption of sedimentation at about 4.1 Ma is associated with a widely recognized Early Pliocene tectonic event involving thrusting and migration of the depocenter of the Northern Apennine foredeep. © 1994.